2016
DOI: 10.3747/co.23.2771
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and Clinical Toxicity Comparison of Critical Organ Preservation with Three-Dimensional Conformal Radiotherapy, Intensity-Modulated Radiotherapy, and RapidArc for the Treatment of Locally Advanced Cancer of the Pancreatic Head

Abstract: Purpose We compared dosimetry and clinical toxicity for 3-dimensional conformal radiotherapy (3D-crt), intensity-modulated radiotherapy (imrt), and RapidArc (Varian Medical Systems, Palo Alto, CA, U.S.A.) in locally advanced pancreatic cancer (lapcc). We hypothesized that the technique with better sparing of organs at risk (oars) and better target dose distributions could lead to decreased clinical toxicity. MethodsThe study analyzed 280 patients with lapcc who had undergone radiotherapy. The dosimetry compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The lack of significant differences in miRNA expression between pre-RT and control groups may indicate that these miRNAs are not tumor-specific in serum/plasma. The VMAT technique achieved highly conformal treatment plans and decreased the normal tissue toxicity compared with other conventional RT techniques (65). Therefore, no significant changes in the miRNA expression levels were observed.…”
Section: Discussionmentioning
confidence: 92%
“…The lack of significant differences in miRNA expression between pre-RT and control groups may indicate that these miRNAs are not tumor-specific in serum/plasma. The VMAT technique achieved highly conformal treatment plans and decreased the normal tissue toxicity compared with other conventional RT techniques (65). Therefore, no significant changes in the miRNA expression levels were observed.…”
Section: Discussionmentioning
confidence: 92%
“…Jin and colleagues analysed DVHs of 20 patients treated for pancreatic cancers and found similar, comparatively low rates of higher grade toxicity. Additionally an advantage of VMAT compared to 3D conformal RT or intensity modulated RT (IMRT) regarding acute toxicities was described by several groups [27,28]. These findings are in contrast to the Phase-I/II study on radiation dose escalation reported by Ben-Josef and colleagues: They observed an increase of dose limiting toxicities with radiation doses higher than 55 Gy [18].…”
Section: Discussionmentioning
confidence: 99%
“…The OARs for sparing included the small intestine, stomach, left kidney, right kidney, liver, and spinal cord. The dose constraints of the OARs were designated in Appendix 16 …”
Section: Tomotherapy Planningmentioning
confidence: 99%